Analisis Perbandingan Hasil Belajar Bahasa Indonesia Melalui Luring SMP Negeri 5 Makassar dan Daring SMP Kartika Wirabuana Makassar - Isnani Arianti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Comparative analysis of Indonesian language learning outcomes through offline SMP Negeri 5 Makassar and online SMP Kartika Wirabuana Makassar. This research is a descriptive type of research that uses a "survey" research design. This study aims to determine; (1) how are the results of learning Indonesian through offline SMP Negeri 5 Makassar; (2) How are the online learning outcomes of Kartika Wirabuana Middle School Makassar; (3) How are the results of learning Indonesian through offline SMP Negeri 5 Makassar and online SMP Kartika Wirabuana Makassar The population is the entire SMP Negeri 5 Makassar Daring SMP Kartika Wirabuana Makassar. The samples used were students of SMP Negeri 5 Makassar Daring SMP Kartika Wirabuana Makassar. as many as 50 people. The technique of determining the sample is by simple random sampling. The data analysis technique used is descriptive analysis. The results showed that; (1) the results of learning Indonesian through offline SMP Negeri 5 Makassar are in the medium category; (2) the results of learning Indonesian through online SMP Kartika Wirabuana Makassar are in the medium category; (1) the results of learning Indonesian through offline SMP Negeri 5 Makassar are better than the results of learning Indonesian through online SMP Kartika Wirabuana.